Calidad postcosecha de pitahaya roja (Hylocereus undatus Haw) y amarilla (Selenicereus megalanthus) en diferentes estados de madurez y temperaturas de conservación - López Vera, Yenny Alexandra (2021)
This research evaluated the post-harvest quality of red pitahaya (Hylocereus undatus Haw) and yellow (Selenicereus megalanthus) in different states of xiv maturity and conservation temperatures. The treatments evaluated were the initial, medium and complete maturity states, at room temperature and controlled (20 Cº). The design consisted of a DCA with six treatments, four replicas and 24 experimental units consisting of 15 fruits. The variables evaluated were weight, diameter, firmness, total soluble solids (Brixº), titrable acidity and ph at 0, 3, 6, 9 and 12 days after harvest. For physical characteristics (weight, diameter, firmness) in red pitahaya no significant differences (p> 0.05) were found, however, in yellow pitahaya fruits these characteristics varied significantly (p <0.05) where the state of full maturity perceived the greatest reduction in these characteristics, however, both genotypes manifested a linear reduction over time, regardless of the states of maturity and temperature. For chemical properties, total soluble solids did not show a specific trend in evaluation time in red and yellow fruits, but statistical difference (p <0.05) was found only in red pitahaya with the initial and average maturity states being controlled temperatures that had the highest Brix. The acidity titrable in red pitahaya had a downward behavior finding statistical differences, with the fruits being in medium maturity at controlled temperature, which reported higher acidity, not so in yellow fruits presented a varied trend of acidity however showing that the controlled temperature directly influenced maintaining high values.